2019
DOI: 10.1016/j.cherd.2019.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble-enhanced DBD plasma reactor: Design, characterisation and modelling

Abstract: The emerging field of atmospheric pressure plasmas (APPs) for treatment of various solutions and suspensions has led to a variety of plasma reactors and power sources. This article reports on the design, characterisation and modelling of a novel plasma-microbubble reactor that forms a dielectric barrier discharge (DBD) at the gas-liquid interface to facilitate the transfer of short-lived highly reactive species from the gas plasma into the liquid phase. The use of microbubbles enabled efficient dispersion of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 56 publications
0
19
0
1
Order By: Relevance
“…Previous studies have demonstrated the effective chemical reaction rates from underwater plasma bubbles translating to remarkably enhanced chemical and biochemical activity for water purification, biomass conversion or biofilm reduction, owing to the high specific interfacial area, high inner pressure and relatively long residence times of plasma bubbles 29 , 49 , 50 . Wright et al modelled the bubbly flow, interfacial mass transfer, transport of species and chemical reactions in the microbubble-DBD reactor and they suggested that the enhanced mass transfer caused a rapid increase and higher final concentrations of reactive species in the liquid phase for the same input conditions to the reactor 51 . The smaller bubble size also influenced the mixing of the liquid, and the fluid velocities induced by the airlift-loop configuration were found to be one order of magnitude larger for smaller bubbles than for larger bubbles 51 .…”
Section: Multiphase Dischargesmentioning
confidence: 99%
“…Previous studies have demonstrated the effective chemical reaction rates from underwater plasma bubbles translating to remarkably enhanced chemical and biochemical activity for water purification, biomass conversion or biofilm reduction, owing to the high specific interfacial area, high inner pressure and relatively long residence times of plasma bubbles 29 , 49 , 50 . Wright et al modelled the bubbly flow, interfacial mass transfer, transport of species and chemical reactions in the microbubble-DBD reactor and they suggested that the enhanced mass transfer caused a rapid increase and higher final concentrations of reactive species in the liquid phase for the same input conditions to the reactor 51 . The smaller bubble size also influenced the mixing of the liquid, and the fluid velocities induced by the airlift-loop configuration were found to be one order of magnitude larger for smaller bubbles than for larger bubbles 51 .…”
Section: Multiphase Dischargesmentioning
confidence: 99%
“…Despite the fact that the highest ozone concentration was achieved with 60% duty cycle (Figure 3), it emerged that the optimum mixture of reactive species for bacterial inactivation was achieved at a 45% duty cycle during the 30-minute operation. The biocidal effects of ROS and RNS have been well established and their production rate depends on the duty cycle used and conditions within the plasma module [19,26]. For a 45% duty cycle, the disinfection level exceeded 5log reductions after a 30-minute treatment time demonstrating the effectiveness of this approach.…”
Section: Reactor Performancementioning
confidence: 99%
“…This is made possible by using a microporous nickel membrane as the sparger as well as the ground electrode (Figure 1(b)). The detailed design and characterization of the reactor have been described in a previous study [14,19], and therefore only a brief description is provided here. The formation of microbubbles in the vicinity of the plasma discharge.…”
Section: Microbubble-gas Plasma Reactor Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas exits the reactor through a port in the centre of the top lid. Further details of the reactor used can be found elsewhere [32].…”
Section: Introductionmentioning
confidence: 99%